Birds of the Sierra Nevada : Their Natural History, Status, and Distribution - Beedy, Edward C. (University of California Press, 2013)
This beautifully illustrated and user-friendly book presents the most up-to-date information available about the natural histories of birds of the Sierra Nevada, the origins of their names, the habitats they prefer, how they communicate and interact with one another, their relative abundance, and where they occur within the region. Each species account features original illustrations by Keith Hansen. In addition to characterizing individual species, Birds of the Sierra Nevada also describes ecological zones and bird habitats, recent trends in populations and ranges, conservation efforts.